The Role of Cutaneous Microcirculatory Responses in Tissue Injury, Inflammation and Repair at the Foot in Diabetes - Balasubramanian, Gayathri Victoria; Chockalingam, Nachiappan; Naemi, Roozbeh (Frontiers in Bioengineering and Biotechnology, 2021)
Diabetic foot syndrome is one of the most costly complications of diabetes. Damage to the soft tissue structure is one of the primary causes of diabetic foot ulcers and most of the current literature focuses on factors such as neuropathy and excessive load. Although the role of blood supply has been reported in the context of macro-circulation, soft tissue damage and its healing in the context of skin microcirculation have not been adequately investigated. Previous research suggested that certain microcirculatory responses protect the skin and their impairment may contribute to increased risk for occlusive and ischemic injuries to the foot. The purpose of this narrative review was to explore and establish the possible link between impairment in skin perfusion and the chain of events that leads to ulceration, considering the interaction with other more established ulceration factors. This review highlights some of the key skin microcirculatory functions in response to various stimuli. The microcirculatory responses observed in the form of altered skin blood flow are divided into three categories based on the type of stimuli including occlusion, pressure and temperature. Studies on the three categories were reviewed including: the microcirculatory response to occlusive ischemia or Post-Occlusive Reactive Hyperaemia (PORH); the microcirculatory response to locally applied pressure such as Pressure-Induced Vasodilation (PIV); and the interplay between microcirculation and skin temperature and the microcirculatory responses to thermal stimuli such as reduced/increased blood flow due to cooling/heating. This review highlights how microcirculatory responses protect the skin and the plantar soft tissues and their plausible dysfunction in people with diabetes. Whilst discussing the link between impairment in skin perfusion as a result of alerted microcirculatory response, the review describes the chain of events that leads to ulceration. A thorough understanding of the microcirculatory function and its impaired reactive mechanisms is provided, which allows an understanding of the interaction between functional disturbances of microcirculation and other more established factors for foot ulceration.